2015
DOI: 10.1093/ehjci/jev067
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac CT angiography for device surveillance after endovascular left atrial appendage closure

Abstract: CCTA appears to be a feasible alternative to transoesophageal echocardiography for post-LAA device surveillance to evaluate for device thrombus, residual leak, embolization, position, and pericardial effusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
116
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 141 publications
(129 citation statements)
references
References 20 publications
3
116
2
Order By: Relevance
“…The diagnosis was based in most cases by TEE FU imaging. Some cases were found on routine CT , one case was suspected on transthoracic echocardiogram (TTE) , and one case was only discovered during coronary artery bypass graft surgery, as it was not seen on previous TTE or TEE .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnosis was based in most cases by TEE FU imaging. Some cases were found on routine CT , one case was suspected on transthoracic echocardiogram (TTE) , and one case was only discovered during coronary artery bypass graft surgery, as it was not seen on previous TTE or TEE .…”
Section: Resultsmentioning
confidence: 99%
“…Diagnosis was made in most cases based on FU TEE as it is the most widely used FU modality. CCTA has also been shown to be an effective surveillance modality . It is important to note that the number of imaging FU performed was significantly correlated with the incidence of DAT.…”
Section: Discussionmentioning
confidence: 99%
“…In WATCHMAN cases, leaks are mostly eccentric and secondary to an edge effect. For ACP/Amulet cases, higher proportion of off-axis lobes were found in cases of patent LAA [31,32] and leaks were more frequent when lobe compression was ≤ 10% [33]. In the presence of peri-device leak ≥5mm, resuming or pursuing antithrombotic therapy or further intervention may be considered.…”
Section: International Journal Of Cardiovascular Practicementioning
confidence: 99%
“…Recently, Main et al have proposed consensus echocardiographic diagnostic criteria for DAT diagnosis: echo density on the LA aspect of the device (1) not explained by imaging artefact; (2) inconsistency with normal healing/device incorporation; (3) visible in multiple TOE planes, (4) in contact with the LAA occluder device; and (5) exhibiting independent motion [53]. CCTA is also able to detect DAT or thrombus on the adjacent LA wall [32].…”
Section: Thrombusmentioning
confidence: 99%
“…CCTA for ACP device follow‐up has been shown to be more reliable than transthoracic echocardiography for assessment of device position and function of ACP . A recent published series by our group included 45 patients with CCTA post LAA closure with the ACP, Amulet and WATCHMAN devices . This case series showed that greater device lobe compression and proper alignment was associated with subsequent complete LAA closure with the ACP and/or Amulet device.…”
Section: Introductionmentioning
confidence: 99%